Bloom - Cronin, Doreen (Atheneum Books for Young Readers, 2016)
When the glass kingdom begins cracking, the king and queen fail in their quest to get help from the fairy Bloom, who can work great magic but was banished because of her muddy boots and messiness, so they send Genevieve, an ordinary girl who will do what it takes to save the day.